Revisiting the social validity of services rendered through a university‐based practicum addressing challenging behavior. Issue 4 (19th June 2022) - Lambert, Joseph M.; Sandstrom, Amanda L.; Hodapp, Robert M.; Copeland, Bailey A.; Paranczak, Jessica L.; Macdonald, M. Janey; Houchins‐Juarez, Nealetta J.
Abstract : This paper represents the third in a three‐part series intended to challenge the social validity of the services provided by a university‐based practicum for addressing the challenging behavior of individuals with disabilities. In this paper, we surveyed referring stakeholders (e.g., parents, teachers) of past service recipients to explore the acceptability of the service model's goals, methods, and outcomes. We probed for tensions resultant from the model's threefold mission (service, training, and research) and explored how conflicts between these goals affected the quality of our services. Generally, results were favorable and appeared to support continued model implementation, but not without qualification. Emergent themes, areas for improvement, and future directions for intervention research are all discussed.